# Proving divergence of a series via Taylor Expansion [closed]

I would like to prove using Taylor expansion that the series $\sum\left(\sqrt{1+\frac{(-1)^n}{\sqrt{n}}}-1\right)$ is divergent for $n\geq 1$. What is the expansion to prove it ?

Thanks

## closed as off-topic by user26857, Claude Leibovici, John B, user91500, WatsonMay 7 '16 at 9:43

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – user26857, Claude Leibovici, John B, user91500, Watson
If this question can be reworded to fit the rules in the help center, please edit the question.

• What makes you think you can prove this with a Taylor Series – Stella Biderman Feb 14 '16 at 15:42
• I'm working with a math book which explains to do it this way without giving the answer – tomas Feb 14 '16 at 15:43
• This is a nice problem is the sense that it' s easy to fool oneself that the series converges if we for example write it on the form $\frac {(-1)^n} {\sqrt {n}} \frac {1} {\sqrt {1 + \frac {(-1)^n} {\sqrt {n}}} + 1}$. The last factor is $\simeq \frac {1} {2}$ so one could naively think that the series should be close to $\frac {(-1)^n} {2\sqrt {n}}$ which converges. However the alternating series test does not apply to the series in question as $\frac {1} {\sqrt {n}} \frac {1} {\sqrt {1 + \frac {(-1)^n} {\sqrt {n}}} + 1}$ does not decrease monotonely. – Winther Feb 15 '16 at 18:05

## 2 Answers

Hint. You may use, as $x \to 0$, the Taylor expansion $$\sqrt{1+x}-1=\frac{x}{2}-\frac{x^2}{8}+O(x^3)$$ giving, for some great $n_0$, and for any $N$ greater than $n_0$,

$$\sum_{n_0 \leq n \leq N } \left( \sqrt{1+\frac{(-1)^n}{\sqrt{n}}}-1\right)=\sum_{n_0 \leq n \leq N } \frac{(-1)^n}{2\sqrt{n}}-\sum_{n_0 \leq n \leq N } \frac{1}{8n}+\sum_{n_0 \leq n \leq N } O\left( \frac{1}{n^{3/2}}\right)$$

then letting $N \to \infty$ leads to the divergence of the series on the left hand side.

• J'adore toujours vos réponses, vous le faites avec tellement d'élégance, c'est fabuleux ! – Hexacoordinate-C Feb 15 '16 at 17:59
• @Shadock Merci pour ce compliment, qui me touche. – Olivier Oloa Feb 15 '16 at 20:03
• Il n'y a pas de quoi, quand je vois la solution de Marthy j'ai envie de dire mais oui bien-sûr haha. France 1 vs EU 0 :-) – Hexacoordinate-C Feb 15 '16 at 23:11

$\begin{array}\\ \sum_{n=1}^{2m} \ \sqrt{1+\frac{(-1)^n}{\sqrt{n}}}-1 &=\sum_{n=1}^{2m} \left( \sqrt{1+\frac{(-1)^n}{\sqrt{n}}}-1 \right) \frac{\sqrt{1+\frac{(-1)^n}{\sqrt{n}}}+1}{\sqrt{1+\frac{(-1)^n}{\sqrt{n}}}+1}\\ &=\sum_{n=1}^{2m} \frac{\frac{(-1)^n}{\sqrt{n}}}{\sqrt{1+\frac{(-1)^n}{\sqrt{n}}}+1}\\ &=\sum_{n=1}^{2m} \frac{(-1)^n}{\sqrt{n}\sqrt{1+\frac{(-1)^n}{\sqrt{n}}}+1}\\ &=\sum_{n=1}^{2m} \frac{(-1)^n}{\sqrt{n+(-1)^n\sqrt{n}}+1}\\ &=\sum_{n=1}^{m} \frac{(-1)^{2n}}{\sqrt{2n+(-1)^{2n}\sqrt{2n}}+1} +\sum_{n=1}^{m} \frac{(-1)^{2n-1}}{\sqrt{2n-1+(-1)^{2n-1}\sqrt{2n-1}}+1}\\ &=\sum_{n=1}^{m} \frac{1}{\sqrt{2n+\sqrt{2n}}+1} -\sum_{n=1}^{m} \frac{1}{\sqrt{2n-1-\sqrt{2n-1}}+1}\\ &=\sum_{n=1}^{m}\left( \frac{1}{\sqrt{2n+\sqrt{2n}}+1} - \frac{1}{\sqrt{2n-1-\sqrt{2n-1}}+1}\right)\\ &=\sum_{n=1}^{m} \frac{(\sqrt{2n-1-\sqrt{2n-1}}+1)-(\sqrt{2n+\sqrt{2n}}+1)}{(\sqrt{2n+\sqrt{2n}}+1)(\sqrt{2n-1-\sqrt{2n-1}}+1)}\\ &=\sum_{n=1}^{m} \frac{\sqrt{2n-1-\sqrt{2n-1}}-\sqrt{2n+\sqrt{2n}}}{(\sqrt{2n+\sqrt{2n}}+1)(\sqrt{2n-1-\sqrt{2n-1}}+1)}\\ \end{array}$

The denominator is $2n+O(\sqrt{n})$.

The numerator is

$\begin{array}\\ \sqrt{2n-1-\sqrt{2n-1}}-\sqrt{2n+\sqrt{2n}} &=\sqrt{2n}\left(\sqrt{1-1/(2n)-\sqrt{1/(2n)-1/(2n)^2}}-\sqrt{1+1/\sqrt{2n}}\right)\\ &=\sqrt{2n}\left(\sqrt{1-1/(2n)-\sqrt{1/(2n)-1/(2n)^2}} -(1+1/(2\sqrt{2n})+O(1/n))\right)\\ &=\sqrt{2n}\left(\sqrt{1-\sqrt{1/(2n)}(\sqrt{1-1/(2n)}+1/\sqrt{2n}} -(1+1/(2\sqrt{2n})+O(1/n))\right)\\ &=\sqrt{2n}\left(\sqrt{1-\sqrt{1/(2n)}((1-1/(4n)+O(1/n^2))+1/\sqrt{2n}} -(1+1/(2\sqrt{2n})+O(1/n))\right)\\ &=\sqrt{2n}\left(\sqrt{1-\sqrt{1/(2n)}((1+1/\sqrt{2n}+O(1/n)} -(1+1/(2\sqrt{2n})+O(1/n)))\right)\\ &=\sqrt{2n}\left((1-\sqrt{1/(8n)}((1+1/\sqrt{2n}+O(1/n)) -(1+1/(2\sqrt{2n})+O(1/n)))\right)\\ &=-\sqrt{2n}\left(2\sqrt{1/(8n)}+O(1/n)\right)\\ &=-1+O(1/\sqrt{n})\\ \end{array}$

Therefore each term is $\frac{-1+O(1/\sqrt{n})}{2n+O(\sqrt{n})} =-\frac1{2n}+O(n^{-3/2})$ and the sum of these diverges.

• I found an error – Hexacoordinate-C Feb 15 '16 at 23:13
• So. What was it? – marty cohen Feb 15 '16 at 23:47
• It was a joke, I will not try to verify, it is a bit hard to read, you should erase the align mod in your second step because it creates "interferences" with the links at the right of the page :) – Hexacoordinate-C Feb 15 '16 at 23:51